The Future of Nuclear Security: A Medical Physicist’s Perspective - Katharine E Thomson (International Journal of Nuclear Security, 2017)
Planning for the future of nuclear security is a vital and complex task, requiring cooperation and contribution from many disciplines and industries. This diversity of expertise should include the medical sector, which faces many of the same challenges as the nuclear industry: controlling access to dangerous material, creating a strong security culture, cooperating with the wider world and engaging the public. Medical physicists, of which the author is one, oversee all aspects of small-scale radiation use. This paper discusses three key areas increasingly important to both medical and nuclear uses of radioactive materials: public engagement, prevention of nuclear and radiological terrorism and cyber security. It compares and parallels practices in both industries and suggests strategies both can take for the future.
Keywords: Nuclear security; medical physics; communication; public engagement; terrorism; cybersecurity